2009
DOI: 10.1007/s00125-009-1621-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postpartum diabetes in women with gestational diabetes mellitus

Abstract: Aims/hypothesis We studied the incidence of postpartum diabetes after gestational diabetes mellitus and investigated biochemical and clinical predictors of postpartum diabetes. Methods We monitored 174 women with gestational diabetes by performing oral glucose tolerance tests during pregnancy as well as 1, 2 and 5 years postpartum. Women who developed impaired fasting glucose, impaired glucose tolerance or diabetes were compared with women who remained normoglycaemic at 5 years. Insulinogenic index, dispositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
81
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 13 publications
15
81
2
4
Order By: Relevance
“…The results of this study showed that high levels of FBS and BMI play an effective role in the development of diabetes, which was consistent with our results (17). What is clear from the analysis of other studies and our study is that high levels of blood sugar during pregnancy is certainly effective and useful in predicting and forecasting the development of diabetes after gestational diabetes.…”
Section: Page 233supporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that high levels of FBS and BMI play an effective role in the development of diabetes, which was consistent with our results (17). What is clear from the analysis of other studies and our study is that high levels of blood sugar during pregnancy is certainly effective and useful in predicting and forecasting the development of diabetes after gestational diabetes.…”
Section: Page 233supporting
confidence: 92%
“…Ekelund et al reported that women who have had abnormal blood glucose levels during pregnancy have assigned higher levels of fasting blood sugar after pregnancy. In this study, a significant relationship between increasing levels of BMI and diabetes after pregnancy was observed (17). Treatment of diabetes and its acute and chronic complications requires significant spending by patients and the healthcare system; further, disability due to this disease is a source of considerable damage at the community level.…”
Section: Introductionmentioning
confidence: 67%
“…Although glucose tolerance usually reverts to normal after delivery, the risk of developing type 2 diabetes following GDM is increased [2], with a cumulative incidence of 30−50% within five to ten years after delivery [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that women who are diagnosed with gestational diabetes mellitus (GDM) have an increased risk of developing type 2 diabetes mellitus (T2DM) in the years after the index pregnancy (1)(2)(3)(4)(5)(6)(7). Furthermore, it is now recognized that even women with milder degrees of glucose intolerance in pregnancy (i.e., less severe than GDM) have an increased risk of ultimately developing prediabetes and T2DM in the future (6,(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%